2023
DOI: 10.1242/dmm.049802
|View full text |Cite
|
Sign up to set email alerts
|

Laforin targets malin to glycogen in Lafora progressive myoclonus epilepsy

Abstract: Glycogen is the largest cytosolic macromolecule and kept in solution through a regular system of short branches allowing hydration. This structure was thought to solely require balanced glycogen synthase and branching enzyme activities. Deposition of overlong-branched glycogen in the fatal epilepsy Lafora disease (LD) indicated involvement of the LD gene products laforin and the E3 ubiquitin ligase malin in regulating glycogen structure. Laforin binds glycogen, and LD-causing mutations disrupt this binding, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…To investigate the expression of malin in the malin-myc mice, we examined skeletal muscle and brain tissues by protein immunoblotting. Unlike the reported Flag-tagged malin that could not be detected in tissue extracts ( 76 ), antibodies against c-myc identified a single protein of the predicted molecular weight, ∼46 kDa (including ∼2.7 kDa of the myc tag), in both skeletal muscle and brain extracts from the malin-myc mice with no reactivity present in wild type (WT) extracts ( Fig. 1 , C and D ).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…To investigate the expression of malin in the malin-myc mice, we examined skeletal muscle and brain tissues by protein immunoblotting. Unlike the reported Flag-tagged malin that could not be detected in tissue extracts ( 76 ), antibodies against c-myc identified a single protein of the predicted molecular weight, ∼46 kDa (including ∼2.7 kDa of the myc tag), in both skeletal muscle and brain extracts from the malin-myc mice with no reactivity present in wild type (WT) extracts ( Fig. 1 , C and D ).…”
Section: Resultsmentioning
confidence: 66%
“…While this article was in preparation, a study describing a mouse model in which the native malin gene is tagged with the FLAG sequence was published ( 76 ). The authors could not detect Flag-malin in tissue extracts or in high-speed pellets, where most of the glycogen is present.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there remains the possibility that LB accumulation, while impressive, is not the proximate cause of neuronal dysfunction related to the loss of malin, whose functions beyond glycogen metabolism remain unknown. We regard this as an unlikely possibility, since recent work has shown that malin’s predominant (if not exclusive) subcellular localization is at glycogen, where it is tightly scaffolded to the carbohydrate binding domain of laforin 11 , the deletion of which produces an identical clinical syndrome. In a number of LD mouse models (including the one studied here), preventing LB formation through downregulation of glycogen synthesis or removing LB by digesting them with a CNS-delivered amylase, prevents or corrects the neuroinflammatory, neurometabolic and brain protein glycation defects that characterize the neuropathology of LD 19,28,65-70 .…”
Section: Discussionmentioning
confidence: 99%
“…LD is caused by mutations in either of two genes located on chromosome 6: EPM2A (encoding laforin, a carbohydrate binding dual-specificity phosphatase 8 ) or NHLRC1 (encoding malin, an E3-ubiquitin ligase 9 ). Current working models of pathophysiology hypothesize that malin and laforin function as a quality control complex within growing glycogen polymers, preventing the generation of very long branches that promote precipitation 1,2,10,11 . A deeper knowledge of these mechanisms remains an active area of research, focusing on a detailed understanding of the substrates of laforin and malin’s phosphatase and E3-ligase activities, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Lafora disease is a rare and fatal epilepsy characterised by the deposition of overlong branched glycogen. A recent study deciphered the role of a glycogen-regulating protein, malin, in the pathogenesis of Lafora disease, which has provided insight into a glycogen metabolism mechanism that may also be involved in more common diseases, such as those involving insulin resistance ( Mitra et al, 2023 ). Furthermore, a study of Paget's disease, a rare bone remodelling disorder, has also unveiled a novel regulator of bone metabolism that has relevance beyond this disorder ( Wani et al, 2022 ).…”
mentioning
confidence: 99%